Risk Assessment Analysis in Boiler System with Hazard and Operability Study (HAZOP) - Rahma, Ratih Andhika Akbar; Hasanudin, Achmad (Department of Industrial Engineering Universitas Muhammadiyah Surakarta, 2023)
PT PJB UBJOM and PLTU Pacitan are using steam power to produce electricity called a Steam Power Plan. The process uses a coal-fired boiler to heat water and produces steam (high-temperature water vapor) to turn a turbine. There is always a risk of crushing injuries, electrical shocks and burns, boiler fires, and explosions, and contact with hazardous chemicals in the work environment, which is frequently hot and noisy and involves several large equipment and processes. The objective of this research is to analyze the risk assessment in Boiler systems with Hazard and Operability Study (HAZOP). Additionally, the usual risk matrix was used to quantify and rank the likelihood and severity of each deviation. The five probability and severity categories are divided into four risk assessment levels by the 5x5 risk matrix. This study uses the risk matrix on PT. PJB standard. According to the results of the Hazard and Operability Study (HAZOP) on PT PJB's boiler system, there are two study nodes with extremely high-risk levels: the feed water setting to the steam drum has a damaged feed water pump, and the steam pressure on the steam drum has a damaged safety valve. As a result, the water level is low, and the boiler trips. The controls implemented by PT PJB are pump repair/ replacement, feed water flow sensor, steam drum level sensor, inspection/ safety valve repair, leak check, sensor level, sensor pressure, and safety valve certification.